CAMPUR KODE PERULANGAN KATA DALAM NOVEL RADIKUS MAKAN KAKUS KARYA: RADITYA DIKA (KAJIAN SOSIOLINGUISTIK) - Sarujin Sarujin (EDU-KATA, 2021)
This study aims to obtain a description of the type and form of mixed reduplication word code in the novel RadikusMakankakus, by RadityaDika. This research data comes from RadikusMakankakus novel, RadityaDika. Data collection in this study using the method refer to the basic techniques of tangible techniques tapping techniques and techniques as advanced techniques. Based on the results of the research, that in the novel RadikusMakankakus, found the type of mixed code into (inner code maxing) and the type of mixed code out (outer code maxing). Type of mixed code into (inner code maxing) found, among others, is mixed code into (inner code maxing) which tangible repetition of Indonesian dialect Jakarta, Javanese words, Jakarta dialect. In addition, also found type of mixed code out (outer code maxing). The outer code maxing types found in the novel include mixing outward code in the form of looping of English words.